Conceptualization of legal reality structure and location of law - Savenko, Viktor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
The article examines the phenomenon of legal reality, as the basis of the deontological being of society and the level of compliance of the legal law with the universal laws of being; analyzes the fundamental principles of the emergence and structure of legal reality; interdependencies between natural law and current legal reality are monitored; the idea that any definition of law contains an ontological basis is substantiated. The article focuses on the fact that the rethinking of laws in modern legal science is formed on the basis of philosophical approaches, among which the most important place is just the right reality as the highest form of systematization of the theory of legal knowledge. System analysis of the law in the structure of legal reality measures the formal implementation of the law of verified decisions. The author concludes that further development of the philosophical understanding of the legal law will go towards enriching its present understanding, which will be synchronized with the ever deeper knowledge in the anthropological, philosophical, social and legal dimensions. The invariability of the fundamental principles of the construction of legal laws is rooted in the fact of their rooting in the transcendental-axiological dimension. Consequently, the relationship between law and law has existed for many years and still exists. This problem was considered both at the international level and at the domestic, modern level. In Ukraine, this issue is relevant and nowadays, which causes great interest and exacerbates the tension in society. This problem is not so much theoretical, as most scholars point out, how practical is it in the process of law-making, law enforcement and law enforcement, since not all laws created by the state, or rather state bodies, have legal content, but sometimes in general they are contrary to it. Therefore, now it is necessary to clearly distinguish between such concepts as legal and illegal law and to understand when the law loses the right to be called illegal, and therefore illegitimate.